Effect of a digital blood pressure coach on hypertension management in primary care practices—a pragmatic, randomised controlled trial - Beger, Christian; Rüegger, Dominik; Lenz, Anna; Wagner, Steffen; Schmidt-Ott, Kai Martin; Volland, Dirk; Limbourg, Florian P. (Frontiers in Digital Health, 2025)
ImportanceSmartphone medical applications (apps) may improve blood pressure (BP) control in the primary care setting in patients with hypertension. However, real-world evidence from primary care is largely lacking.ObjectiveTo analyse, in primary care practices in Germany, the effect of a smartphone app on systolic BP compared to standard of care.DesignA pragmatic, non-blinded randomized controlled trial with patients with a diagnosis of hypertension was conducted across 23 general practices in Germany, with a follow-up period of 3 months. Recruitment occurred from January 2022 to May 2023.InterventionThe intervention group received access to the Manoa app, a smartphone coach integrating guideline-compliant home BP monitoring and lifestyle-coaching. All study participants received standard treatment for arterial hypertension at the discretion of the treating physician.Main OutcomesThe primary outcome was office systolic BP (oSBP) after 90–150 days in participants with uncontrolled hypertension (oSBP ≥140 mmHg). Secondary outcomes included changes in systolic and diastolic BP, BP control and adherence to home blood pressure monitoring.ResultsA total of 606 participants from 23 general practices were randomized, after data clearance and review, 249 participants were assigned to the control group and 259 to the intervention group for analysis. The mean age (SD) of participants in the intervention group was 55.9 (12.9) years. At baseline, participants with uncontrolled hypertension had a mean oSBP (SD) of 152.6 (14.2) mmHg in the intervention group (n = 162) and 152.6 (14.1) mmHg in the control group (n = 147). After 120 ± 14 days, oSBP decreased to 137.4 (14.4) mmHg in the intervention group and to 137.7 (14.5) mmHg in the control group, with a between-group mean difference of −0.2 mmHg [95% CI (−3.9,3.5); P =.9]. At the follow-up appointment, 69.1% of participants in the intervention group submitted a BP-diary, compared to 36.1% in the control group [OR = 3.95; 95% CI (2.73,5.72); P = <0.001].Conclusions and RelevanceParticipants with uncontrolled hypertension randomized to an app in primary care achieved similar decreases in systolic BP but higher adherence to home BP monitoring compared to standard care. In this open-label, pragmatic trial, variability in hypertension management strategies and limited standardization across practices may have confounded the precise evaluation of digital intervention benefits. Clinical Trial RegistrationClinicalTrials.gov, identifier, (DRKS00027964)